LIGHTWEIGHT-ORIENTED OPTIMIZATION DESIGN ON LEAF SPRING CLAMP OF HEAVY-TRUCK - ZHANG Bing; WANG ZongYan; LU ChunYue; WANG Ke (Jixie qiangdu)
According to the requirement of the enterprise that the raw material of leaf spring clamp is replaced from QT500-10 to ZG650-830,in order to reduce costs,lightweight design is needed as a result. Based on the parametric finite element model of leaf spring clamp established by the adoption of ANYSYS Workbench,this article takes relevant parameters of the inner chamber as design variable,generates design parameter sample space through experimental design and confirms the optimization direction of structural parameters by acquiring the response surface of sample point from finite element solution as well as the conduction of sensitivity analysis on the design variable. Multiplication and division methods are adopted to conclude mathematical model of multi-objective optimization. And the Workbench is also applied for the size optimization design,acquiring a one-time lightweight leaf spring clamp model. Then,further topological optimization is conducted on one-time lightweight model to acquire the final one. This research shows that the leaf spring clamp after lightweight design can meet the requirements of intensity and stiffness with higher safety performance in structure,and the weight reduction ratio also amounts to 26. 78%compared with the original structure.